PENGARUH JUMLAH PENDUDUK DAN PENDAPATAN PERKAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) (Provinsi Jawa Timur Periode 2017-2019) - Abd Adim (Jurnal Ekonomi dan Bisnis, 2021)
During the era of regional autonomy and fiscal decentralization, local governments were given the authority to increase their revenues and to carry out an allocative function in setting regional development priorities. This study aims to examine the effect of government spending, per capita income on the Human Development Index (HDI) at the district / city level of East Java Province. The study population consisted of 38 districts and municipalities, using secondary data from the Central Statistics Agency of East Java Province and the Regency / City level of East Java Province in the 2017-2019 period. Data analysis was performed using the Fixed Effect Model (FEM) with the Eviews software program. The results of this study indicate that the first per capita income has a positive and significant effect on the human development index in districts / cities at the level of East Java Province. Second, the population has not had a significant effect on the human development index at the district / city level in East Java Province.